An investigation of the Peutz-Jeghers gene (LKB1) in sporadic breast and colon cancers. Issue 10 (1st October 2000) - Forster, L F; Defres, S; Goudie, D R; Baty, D U; Carey, F A
Abstract : Aims —To explore the role of the Peutz-Jeghers gene (LKB1) in sporadic breast and colon cancers. Methods —Thirty consecutive sporadic carcinomas of the breast and 23 of the colon were selected. DNA was extracted from paraffin wax embedded tissue and analysed for loss of heterozygosity (LOH) at microsatellite markers D19S886 and D19S565 close to the LKB1 gene. Tumours showing LOH were screened for LKB1 mutations by single strand conformational polymorphism (SSCP). Results —Five breast carcinomas showed LOH (21% and 7% of those informative for D19S886 and D19S565, respectively). Five of the colorectal carcinomas showed LOH (15% and 36% of those informative for D19S886 and D19S565, respectively), with one sample showing allele loss with both markers. Screening of these 10 carcinomas by SSCP identified one migrational shift but sequencing revealed an intronic polymorphism only. Therefore, no coding mutations were found in these carcinomas. Conclusions —These findings suggest that although allele loss at the LKB1 locus occurs relatively frequently in sporadic breast and colon cancers, mutations do not seem to be a feature.